Rural Fish Enterprise Growth Based on Entrepreneurial Practices in Tanzania (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: The research aimed to compare the growth of rural fish enterprises among the fish traders in the Misungwi and Magu districts. Precisely, the research fulfilled objectives are to (i) establish associations between fish traders’ innovation mindset, market orientation and risk-taking and (ii) establish if a statistical difference exists between Misungwi and Magu enterprises owned by fish traders.Design/Methodology/Approach: This research was cross-sectional, using a sample of 297 fisher and fish traders from the Misungwi and Magu districts in the Mwanza region along Lake Victoria. The sample choice procedure was proportionate stratified sampling, given that the populations of fishers and fish traders in the Misungwi and Magu districts differed. Crosstab was performed to generate Chi-Square values to measure associations among associated variables. Further, computations of Phi coefficients were undertaken to measure the size effect of the associations established. An independent samples t-test afterwards was conducted to estimate the differential existence of rural fish enterprises between Misungwi and Magu fish traders.Findings: The results further illustrate that statistically, the age of fish traders, experience in business, startup capital, capital invested in 2023 and number of employees at start-up were different between Misungwi and Magu fish traders and their differences using Eta Squared were estimated to be small for age of fish traders, experience in business and number of employees while that of startup capital invested and capital invested in 2023 were moderate.Research Limitation: Due to time and financial resources, the research was restricted to Misungwi and Magu districts in the Mwanza region and adopted only quantitative data capture.Practical Implication: The results will inform the industry's formulation of collaborative programmes for capacity building for fish traders in financial management, marketing, and entrepreneurship.Social Implication: A flourishing Fisher enterprise will have a spillover effect on the rural community by increasing the employment rate and livelihood.Originality/ Value: This research represents a significant advancement in understanding and developing rural fish enterprises through entrepreneurial approaches, filling a crucial gap in academic literature and practical implementation.
Keywords: Comparative. entrepreneurial. fish enterprise. lake victoria. Tanzania